Who Marries Whom? : Educational Systems as Marriage Markets in Modern Societies - Blossfeld, Hans-Peter (European studies of population, 2003)
The book is theoretically driven and combines demographic and sociological approaches with rational choice theory to explain assortative mating. Using life-history data from a broad range of industrialized countries and longitudinal statistical models, the book analyzes the process of spouse selection in the life courses of single men and women. The countries included vary widely in important characteristics such as demographic behavior and institutional characteristics. The life course approach explicitly recognizes the dynamic nature of partner decisions, the importance of educational roles and institutional circumstances as young men and women move through their life paths, and the accumulation of advantages and disadvantages experienced by individuals.